The National Health Assembly, a way to increase community participation in health decision making - Farshad, Ali Asghar; Rostamigooran, Narges (Social Determinants of Health, 2016)
Health is the result of dynamic and complicated relationships and deals with non-linear and non-predictable procedures. Nowadays, the health section cannot solely solve its challenges. Changing the load of diseases toward noncommunicable diseases all over the world including developing countries, and the fact that development of such diseases has complicated mechanisms and is dependent on several factors made us consider the importance of doing some health based interferences in other sections more than before (1,2).